2017
DOI: 10.1038/s41528-017-0004-y
|View full text |Cite
|
Sign up to set email alerts
|

Buckling analysis in stretchable electronics

Abstract: In the last decade, stretchable electronics evolved as a class of novel systems that have electronic performances equal to established semiconductor technologies, but can be stretched, compressed, and twisted like a rubber band. The compliance and stretchability of these electronics allow them to conform and mount to soft, elastic biological organs and tissues, thereby providing attractive opportunities in health care and bio-sensing. Majority of stretchable electronic systems use an elastomeric substrate to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…Kinetic growth of the wave/wrinkle includes three stages: initial growth, coursing, and equilibrium, which can be quantitatively understood by the combination of liner perturbation analysis and energy minimization . Both single‐ and multiwave patterns can occur ( Figure a), corresponding to the global and local buckling modes of the hybrid system, respectively . Critical factors that separate these two modes are the modulus and thickness ratio between the substrate and the inorganic thin film .…”
Section: Structural Designs For Soft Electronicsmentioning
confidence: 99%
“…Kinetic growth of the wave/wrinkle includes three stages: initial growth, coursing, and equilibrium, which can be quantitatively understood by the combination of liner perturbation analysis and energy minimization . Both single‐ and multiwave patterns can occur ( Figure a), corresponding to the global and local buckling modes of the hybrid system, respectively . Critical factors that separate these two modes are the modulus and thickness ratio between the substrate and the inorganic thin film .…”
Section: Structural Designs For Soft Electronicsmentioning
confidence: 99%
“…In the case of "hard" PV and/or conducting layers such as silicon, perovskite, and indium tin oxide, various ways of fabricating them onto an instability-driven wrinkled base structure, for the purpose of enhancing light trapping (Ram et al, 2017;Bush et al, 2018;Schauer et al, 2018;Zhang et al, 2018) or scattering (Wang C. et al, 2017), have been reported. An added benefit of the wrinkled structure is the possible improvement in deformability in stretchable electronics (Wang B. et al, 2017); thus enabling their potential deployment in fabrics and on curved or uneven surfaces. Some recent studies have demonstrated the mechanical robustness upon stretching, bending, and cyclic deformation while retaining reasonable optoelectronic performances (Kaltenbrunner et al, 2012;Hsieh et al, 2018;Ryu and Mongare, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the substrate also affects the buckling structures in practical applications, which is not considered in the above theory . More complicated buckling theories are reviewed elsewhere for interested readers …”
Section: Fabrication Of Buckled Structuresmentioning
confidence: 99%